TELAAH THE HOLY QURâAN KARYA ABDULLAH YUSUF ALI - Ibrahim, Sulaiman (Institut Agama Islam Negeri (IAIN) Palu, 2010)
This article deals with The Holy Qurâan, a book of translation and of a quranic exegeses written by Â Abdullah Yusuf Ali. This book becomes popular since it not only uses international language (English), but also possesses its own characteristics which make it different from other books of Â exegeses.Â The Holy Qurâan is so dominant in its sufistical commentary that it employes esetoric hermeneutics over the symbols existing in the Qurâan. In addition, this book employs lexical, grammatical, contextual, and social-cultural meanings that convey message that the translator depends on the standard language of the Qurâan. Abdullah Yusuf Ali obey does not the literal meanings of the verses, but he puts stongger emphases on its spiritual meanings.Kata Kunci: The Holy Qurâan, Abdullah Yusuf Ali, kitab tafsir Â Â